A meaningful MESS (Medical Education Scholarship Support). Issue 1 (1st January 2016) - Whicker, Shari A.; Engle, Deborah L.; Chudgar, Saumil; DeMeo, Stephen; Bean, Sarah M.; Narayan, Aditee P.; Grochowski, Colleen O'Connor; Nagler, Alisa
Abstract : Background: Graduate medical education faculty bear the responsibility of demonstrating active research and scholarship; however, faculty who choose education-focused careers may face unique obstacles related to the lack of promotion tracks, funding, career options, and research opportunities. Our objective was to address education research and scholarship barriers by providing a collaborative peer-mentoring environment and improve the production of research and scholarly outputs. Methods: We describe a Medical Education Scholarship Support (MESS) group created in 2013. MESS is an interprofessional, multidisciplinary peer-mentoring education research community that now spans multiple institutions. This group meets monthly to address education research and scholarship challenges. Through this process, we develop new knowledge, research, and scholarly products, in addition to meaningful collaborations. Results: MESS originated with eight founding members, all of whom still actively participate. MESS has proven to be a sustainable unfunded local community of practice, encouraging faculty to pursue health professions education (HPE) careers and fostering scholarship. We have met our original objectives that involved maintaining 100% participant retention; developing increased knowledge in at least seven content areas; and contributing to the development of 13 peer-reviewed publications, eight professional presentations, one Masters of Education project, and one educational curriculum. Discussion: The number of individuals engaged in HPE research continues to rise. The MESS model could be adapted for use at other institutions, thereby reducing barriers HPE researchers face, providing an effective framework for trainees interested in education-focused careers, and having a broader impact on the education research landscape.